La Importancia Del Control Interno Y Su Efectividad Empresarial (2022)
The importance of internal control and its business effectiveness contribute to the organization, consolidation and above all to foresee internal or external risks that may harm the company and the achievement of its objectives. Therefore, this article was carried out to demonstrate the importance of internal control which is indispensable for all companies regardless of their size, this system is used nationally and internationally, in addition, large corporations implement it because it is a constant help, monitoring and rigorous evaluation in order to avoid making mistakes that may affect the company internally or externally. The research is of qualitative type, a review of the literature on the subject was made and it is intended to demonstrate why it is indispensable, likewise, the business effectiveness resulting from the implementation of internal control systems was analyzed. In Colombia many companies close in their early years because they do not foresee risks that may affect them, or they make bad decisions about the direction of the company and generate that the company reports losses and finally bankruptcy, this can be mitigated by internal control because one of its main functions is to advise, ensure compliance with laws, support, evaluate, verify, monitor, supervise, inspect, design methods or mechanisms that contribute to making decisions that benefit the company and thus avoid errors that may harm it.